2017
DOI: 10.1038/nature22821
|View full text |Cite|
|
Sign up to set email alerts
|

Microglia-dependent synapse loss in type I interferon-mediated lupus

Abstract: Systemic lupus erythematosus (SLE) is an incurable autoimmune disease characterized by autoantibody deposition in tissues such as kidney, skin and lungs. Notably, up to 75% of patients with SLE experience neuropsychiatric symptoms that range from anxiety, depression and cognitive impairment to seizures and, in rare cases, psychosis-collectively this is referred to as central nervous system (CNS) lupus. In some cases, certain autoantibodies, such as anti-NMDAR or anti-phospholipid antibodies, promote CNS lupus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
150
1
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(163 citation statements)
references
References 38 publications
10
150
1
1
Order By: Relevance
“…Upregulation of CD68 immunoreactivity indicates enhanced phagocytic activity in microglia and can be related to increased synapse engulfment [16, 28]. In the current study, we showed a linear relationship between loss of synaptic proteins and CD68 immunoreactivity, suggesting orthopedic surgery increases microglial phagocytosis of hippocampal synapses.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Upregulation of CD68 immunoreactivity indicates enhanced phagocytic activity in microglia and can be related to increased synapse engulfment [16, 28]. In the current study, we showed a linear relationship between loss of synaptic proteins and CD68 immunoreactivity, suggesting orthopedic surgery increases microglial phagocytosis of hippocampal synapses.…”
Section: Discussionsupporting
confidence: 61%
“…Notably, upregulation of microglial phagocytic activity has been related to increased synapse engulfment [16, 20, 28]. Here, we showed a significant correlation between microglial CD68 expression and synapse numbers (SYP: r  = − 0.606, p  = 0.017, Fig.…”
Section: Resultssupporting
confidence: 51%
“…This is also supported by IPA that showed that a number of genes expressed in astrocytes and microglia are known to contribute to neurological diseases. Further, the common IFN-I response in treated microglia shows some functional similarities (such as genes required for sensing endogenous molecules and pathogens) to recently reported changes in gene expression in microglia from a mouse model of CNS lupus (Bialas et al, 2017), an IFN-a-associated disease. Further, the common IFN-I response in treated microglia shows some functional similarities (such as genes required for sensing endogenous molecules and pathogens) to recently reported changes in gene expression in microglia from a mouse model of CNS lupus (Bialas et al, 2017), an IFN-a-associated disease.…”
Section: Color Online and Bw In Printsupporting
confidence: 61%
“…These mice develop characteristic signs of SLE, due to the production of polyreactive autoantibodies against ssDNA, RNA, and nucleosomes, and activation of the IFN‐I response (Berland et al, ; Das et al, ; Han et al, ). They also show significant neurological deficits, with poor performance in cognitive and behavioral tasks, which are rescued by treatment with anti‐IFNAR antibody (Bialas et al, ). The 564Igi mice show an IFN‐I‐dependent increase in the number of reactive microglia in the CNS (Bialas et al, ).…”
Section: The Response Of Microglia In Il‐6‐ and Ifn‐i‐mediated Neuroimentioning
confidence: 99%
“…They also show significant neurological deficits, with poor performance in cognitive and behavioral tasks, which are rescued by treatment with anti‐IFNAR antibody (Bialas et al, ). The 564Igi mice show an IFN‐I‐dependent increase in the number of reactive microglia in the CNS (Bialas et al, ). Microglia also phagocytose neuronal synapse material in an IFN‐I‐dependent manner, contributing to the reduction of synaptic density in the frontal cortex of the 564Igi mice (Bialas et al, ).…”
Section: The Response Of Microglia In Il‐6‐ and Ifn‐i‐mediated Neuroimentioning
confidence: 99%